No Child Left Behind. Universal Child Care and Children's Long-Run Outcomes - Tarjei Havnes; Magne Mogstad (Statistics Norway, Research Department, 2009)
There is a heated debate in the US and Canada, as well as in many European countries, about a move towards subsidized, universally accessible child care. At the same time, studies on universal child care and child development are scarce, limited to short-run outcomes, and the findings are mixed. We analyze the introduction of subsidized, universally accessible child care in Norway, addressing the impact on the long-run outcomes of children. Our precise difference-in-difference estimates show that child care had strong positive effects on children's educational attainment and labor market participation, and also reduced welfare dependency. 17,500 new child care places produces around 6,200 additional years of education. In line with these results, we find that children exposed to child care delay child bearing and family formation as adults. Subsample estimations by child's sex and mother's education suggest that good access to subsidized child care levels the playing field. A battery of specification checks support our empirical strategy.
Keywords: J13; H40; I28; 330; Universal child care; child development; long-run outcomes; difference-in-difference